Pelatihan Meningkatkan Motivasi Belajar Siswa Melalui Metode Ice Breaking di SDN 32 Bacukiki, Pare Pare, Sulawesi Selatan - Hasbi, Hasbi; Wahrini, Retyana (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
One period that is quite important is when children enter elementary school. One of the things that can be introduced to elementary school children is the concept of ideals. Here, we can introduce and explain how the description of the profession can be his dream. Conventional learning that is often carried out by teachers in a classroom atmosphere tends to be teacher-centered, so that students become passive, bored, and lack motivation to achieve the goals given by the teacher. Therefore, a training was held on providing motivation for elementary school children by using the Ice Breaking Method for Students of SDN 32 Bacukiki Parepare, so that efforts to improve students' abilities to achieve the goals they dream of through the Ice Breaking Method are made the best use of to motivate themselves to continue their education and increase enthusiasm in the learning process.